1984
DOI: 10.2118/10822-pa
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Effect of CO2 Injection on the Recovery of In-Situ Methane From Bituminous Coal: An Experimental Simulation

Abstract: A set of experiments is described in which CO2 is injected into large cores of CH4- and water-saturated bituminous coal at elevated pressures. CO2 at Pressures up to 800 psig [5516 KPa] is used to simulate the enhanced recovery of in-situ CH4 from coal beds. CO2 injection increases the recovery of CH4 by a factor of two to three times that achieved in simple desorption by pressure drawdown and atmospheric diffusion. In pressure drawdown and atmospheric diffusion. In general, higher CO2 pressures achieve greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 3 publications
4
50
0
Order By: Relevance
“…The injected CO 2 was able to completely strip the adsorbed methane. Reznik et al (10) carried out a set of experiments and injected CO 2 at different pressures into large cores to methane and water-saturated bituminous coal, and further conducted a simulation study to calculate the increase in recovery of methane. CO 2 injection increased the recovery of methane by a factor of two to three times that achieved by pressure drawdown.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The injected CO 2 was able to completely strip the adsorbed methane. Reznik et al (10) carried out a set of experiments and injected CO 2 at different pressures into large cores to methane and water-saturated bituminous coal, and further conducted a simulation study to calculate the increase in recovery of methane. CO 2 injection increased the recovery of methane by a factor of two to three times that achieved by pressure drawdown.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Figures 1 and 2 the pressure variations vs. time are reported. The parameter on the y axis is the unaccomplished pressure change and it is defined as follows (Walker, 1981):…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, at that time it was concluded that such a proposition would not be practical because it had been reported (Reznik et al, 1984) that an "excessive" amount of CO 2 would be required to displace the adsorbed methane. Today, with the greenhouse effect on our minds, this "excessive" amount is viewed as an attractive feature of CO 2 sequestration in coal mines.…”
Section: Uptakes and Differential Adsorption Heats Of Co 2 Vs Ch 4 Imentioning
confidence: 99%
“…With respect to the difference in the adsorption of CO 2 and CH 4 , some laboratory experiments have shown that more CO 2 is adsorbed in coal than CH 4 under the same conditions, and CO 2 may displace CH 4 adsorbed by coal (Reznik et al 1984;Zuber 1998;Clarkson and Bustin 2000;Wu and Guo 2001;Zhang et al 2005;Tang et al 2006;Lv et al 2011). With respect to coal matrix expansion and permeability changes due to CO 2 adsorption, mathematical and physical models of coal matrix expansion and contraction during the adsorption/desorption process based on surface chemistry and elastic mechanics theories have been confirmed with experimental data (Wu et al 2005;Zhou et al 2011;Ni et al 2013).…”
Section: Introductionmentioning
confidence: 99%